Method and system for steganography within handwritten signature images - Syed Ahmad Abdul Rahman, Sharifah Mumtazah; Wan Adnan, Wan Azizun (2013)
A method for encoding a text message within a handwritten signature includes the steps of pre-processing the handwritten signature for preparing the signature into a suitable format for extracting at least one attribute of the handwritten signature, extracting the at least one attribute of the handwritten signature from the suitable format, coding the text message into a pre-defined coding format and encrypting the text message into an encrypted code and embedding the encrypted code of the text message within the at least one attribute extracted from the handwritten signature. The step of embedding of the encrypted code of the text message includes inspecting multiple pixel blocks of the handwritten signature and modifying multiple pixel blocks of the handwritten signature in accordance with the encrypted code of the text message.